Financial management among Academy of Contemporary Islamic Studies students in UiTM Puncak Alam / Zuriatul Afini Yusaini. - Yusaini, Zuriatul Afini (2020)
The study is about the financial management among Academy of Contemporary Islamic Studies (ACIS) students in University Teknologi Mara (UiTM) Puncak Alam. This study is given the priority to ACIS students who have two courses namely Diploma in Muamalat and Diploma in Halal Management. It is focused only for the semester 5. The total number of students involved is more than 195 (population) but however this study takes only 195 (samples) over 195. This is due to short time and difficult to make aa comparison on it. This study used the method quantitative to get the result which is by questionnaire. The questionnaire distributed by online through WhatsApp personal and WhatsApp group. Financial management is one of the significant aspects that every student needs to master in managing financial resources and daily expenses. Without systematic management, various problem will arise. Awareness in financial management needs to be nurtured and constantly enhanced in every student. When it comes to consciousness, then the students are able to improve their own mistakes and weaknesses. Students will also be better prepared to be guided and to enhance personal financial performance towards a more systematic and prudent spending.